2001
DOI: 10.1007/s002130000583
|View full text |Cite
|
Sign up to set email alerts
|

Three sets of diagnostic criteria for major depression and correlations with serotonin-induced platelet calcium mobilization in cancer patients

Abstract: These findings, based on the use of enhanced serotonin-induced platelet calcium mobilization as a biological marker, suggest that the exclusive approach might be the most valid and appropriate method of diagnosing major depression in cancer patients, while the inclusive and substitutive approaches might overestimate the occurrence of major depression in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These results support previous studies that showed removing somatic items reduced the rates of depression in people with cancer (Grassi & Rosti, 1996; Ryan et al, 2012; Uchitomi et al, 2001). However, our results support the continued use of somatic symptoms in the assessment of depression with caution when sleep disturbance or fatigue is reported during active treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results support previous studies that showed removing somatic items reduced the rates of depression in people with cancer (Grassi & Rosti, 1996; Ryan et al, 2012; Uchitomi et al, 2001). However, our results support the continued use of somatic symptoms in the assessment of depression with caution when sleep disturbance or fatigue is reported during active treatment.…”
Section: Discussionsupporting
confidence: 92%
“…These studies suggest that utilizing substitutive or exclusive criteria leads to lower prevalence of MDD than DSM-IV criteria (Grassi & Rosti, 1996; Ryan, Gallagher, Wright, & Cassidy, 2012; Uchitomi et al, 2001). However, some studies suggest somatic symptoms may still provide useful information especially for screening (Akechi et al, 2009; Mitchell, Lord, & Symonds, 2012; Traeger et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Delisi et al [239] found that the increase in the 5HT 2A receptor-mediated Ca 2+ response was greater in platelets of depressed patients with higher anxiety than those with low anxiety. The importance of Ca 2+ in depression is further supported by recent studies showing increased serotonin-induced Ca 2+ mobilization in platelets of depressed patients [240,241]. On the other hand, Kusumi et al [242] recently showed that depressed patients with an enhanced Ca 2+ response to 5HT in platelets exhibit a good response to mood stabilizers (bipolar patients) but that those with major depression showed a poor response to antidepressants.…”
Section: Calcium Regulation In Mood Disordersmentioning
confidence: 93%
“…Diminished activity of forskolin-stimulated platelet adenylyl cyclase [48] has also been observed. Additionally, enhanced 5-HT-induced platelet calcium mobilization can be used as a biological marker when investigating the pathophysiology of major depression [49]. Other platelet receptors, such as the glutamate receptors, may work at a higher level of sensitivity in depression, too.…”
Section: Depression and Plateletsmentioning
confidence: 99%